Rational ligand choice extends the SABRE substrate scope - Colell, Johannes F. P. (Chem Commun (Camb), 2020)
Signal Amplification By Reversible Exchange (SABRE) is a particularly simple hyperpolarisation approach. However, compared to other hyperpolarisation methods, SABRE is more limited in substrate scope. Therefore, it is critical to understand and overcome the factors limiting generalization. Past developments in SABRE catalyst optimization have emphasized large enhancements in the canonical SABRE substrate: pyridine and structurally closely related motifs. However, the pyridine-optimized catalysts are not efficient at hyperpolarising more sterically demanding substrates, including 2-substituted pyridine derivatives. Here we report that modifications of the catalyst ligand sphere, using a chelating ligand in particular, can increase the volume fraction available for substrate coordination to the iridium catalyst, thus permitting significant signal enhancements on otherwise sterically hindered substrates. The system yields (1)H enhancements on the order of 100-fold over 8.5 T thermal measurements for 2-substituted pyridine derivatives, and smaller, yet significant (1)H enhancement for provitamin B(6) and caffeine. For the 2-substituted pyridine derivatives we further show (15)N enhancements on the order of 1000-fold and (19)F enhancements of 30-fold over 8.5 T thermal polarisations.